KESETARAAN GENDER PERSPEKTIF PEMIKIRAN ISLAM - Muh. Rusli (Yinyang: Jurnal Studi Islam Gender dan Anak, 2011)
Abstract; Gender is an issue that still leaves the problem at the level of social reality, is is caused by social constructs and preserved through a mistake of interpretation of religious teachings, cultural values, parents, educational systems, and legal norms. Gender insjustice can only be minimixed with a pass up the reconstruction of understanding and transfer of ideas to grassroots level. Keywords: Reconstruction, Gender Equality, and Understanding